2016
DOI: 10.14419/ijdr.v4i1.5986
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial activity of biodentine and MTA against e. faecalis an in vitro study

Abstract: Background: Surgical endodontic therapy is the prescribed treatment of choice whenever the non-surgical options fail which includes the use of a root end filling material. E. faecalis is the most prevalent organism associated with the treatment failed cases Aim: The purpose of the present study was to evaluate and compare the antimicrobial efficacy of Biodentine and MTA as root end filling material and root repair material against E. faecalis. Settings and Design: Comparative invitro study was conducted at Tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…According to Bhavana V et al [44] , Biodentine had higher antimicrobial activity against E. faecalis, C. albicans, S. mutans than MTA. Similar data concerning higher antimicrobial activity was found in Biodentine in comparison to MTA [42,43,[45][46][47][48] . The latter author found that Biodentine has a higher antifungal capacity in C. albicans when compared to MTA.…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…According to Bhavana V et al [44] , Biodentine had higher antimicrobial activity against E. faecalis, C. albicans, S. mutans than MTA. Similar data concerning higher antimicrobial activity was found in Biodentine in comparison to MTA [42,43,[45][46][47][48] . The latter author found that Biodentine has a higher antifungal capacity in C. albicans when compared to MTA.…”
Section: Methodssupporting
confidence: 78%
“…According to Jerez-Olate et al, Biodentine has higher antibiofilm action for a prolonged aging period in the in vitro Modified Direct Contact Test than ProRoot MTA [41] . According to Vaki et al and Jose et al, the agar diffusion test found a higher diameter of inhibition zones in the group of Biodentine in comparison to MTA [42,43] .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some studies showed that MTA, CEM cement, and Biodentine have antibacterial effect on E. faecalis , but different studies showed different significance [ 40 , 41 ]. So, in this study, we consider antibacterial effects for all coronal plugs without any significant differences which may be present.…”
Section: Discussionmentioning
confidence: 99%